Fatal amoebic meningoencephalitis caused by Balamuthia mandrillaris in Pongo pygmaeus and first case report in Pan troglodytes verus - Rodríguez-Expósito, Rubén L.; Carbonell, Loles; Recuero-Gil, Jesús; Martinez, Javier; Martinez-Valverde, Rosa; Martinez-Fernandez, Carmen; Ortega-Porcel, Joaquín; Hernández, Agustín Barragán; Corpa, Juan M.; Cortijo, Estefanía Montero; Sánchez-Nicolás, Jesús; Moya, Sergio; et al. (Frontiers in Veterinary Science, 2025)
Balamuthia mandrillaris is an amoeba that can cause granulomatous amoebic encephalitis (GAE) as well as lung and skin infections in both humans and animals. Studies on B. mandrillaris-related GAE cases have increased in recent years. This amoeba has been identified as a cause of encephalitis and death in several non-human primates. In this study, we report a case of a 4-year-old female Bornean orangutan (Pongo pygmaeus) in a zoological center that exhibited neurological symptoms for several days. After unsuccessful treatments and a worsening in her condition, euthanasia was deemed necessary. Additionally, we describe the case of a 4-year-old male chimpanzee (Pan troglodytes verus) who died suddenly in a different zoo. Postmortem analysis revealed brain lesions with multiple hemorrhages, oedema, and inflammation in various organs in both cases. Histology showed the presence of B. mandrillaris trophozoites in necrotic and inflamed brain tissues, consistent with granulomatous amoebic meningoencephalitis. The diagnosis was confirmed using a multiplex qPCR assay on brain tissue samples from both animals water and soil samples from the chimpanzee’s and orangutan’s enclosure tested positive for B. mandrillaris DNA by qPCR, confirming environmental exposure. An immunofluorescent antibody (IFA) assay detected B. mandrillaris in chimpanzee brain slices. According to the authors’ knowledge, this report documents the first known cases of Balamuthia amoebic encephalitis in non-human primates in Spain and the first case in Pan troglodytes verus.